Exploring English Language Education Major University Lecturers’ and Students’ Perceptions of AI-Based Applications in Post-Pandemic Learning - Yohana Nova Enzelina; Made Hery Santosa; A.A. Gede Yudha Paramartha (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
This study investigated the lecturers’ and students’ perceptions and examined the affordances and challenges of AI-based applications in post-pandemic learning. The subject of this research is 6 lecturers and 211 sixth-semester students in English Language Education at Universitas Pendidikan Ganesha. The research method used was the Explanatory Sequential Mixed-Method. The questionnaire was used to investigate lecturers’ and students' perceptions. Furthermore, the interview method was used as a follow-up to some questionnaire respondents. This research contributed to the following questions: (1) the perceptions of lecturers and students of AI-based applications in post-pandemic learning, and (2) the affordances and challenges of AI-based applications in post-pandemic learning. The findings showed that the students tend to have positive perceptions of AI-based applications. The students think that AI-based applications are innovative and helpful for improving learning English skills. However, lecturers tend to have negative perceptions in a few statements regarding AI-based applications in post-pandemic learning. The lecturers think that the implementation of AI-based applications must still take into consideration student motivation, pedagogical competence, and technological competency. Through this study, the lecturer will get information to design effective and efficient learning objectives using AI-based applications and the students could learn how to improve their English language learning skills.